Self-organized criticality : emergent complex behavior in physical and biological system - Jensen, Henrik Jeldtoft (Cambridge : Cambridge University Press, 1998)
Self-organized criticality (SOC) is based upon the idea that complex behavior can develop spontaneously in certain multi-body systems whose dynamics vary abruptly. This book is a clear and concise introduction to the field of self-organized criticality, and contains an overview of the main research results. The author begins with an examination of what is meant by SOC, and the systems in which it can occur. He then presents and analyzes computer models to describe a number of systems, and he explains the different mathematical formalisms developed to understand SOC. The final chapter assesses the impact of this field of study, and highlights some key areas of new research. The author assumes no previous knowledge of the field, and the book contains several exercises. It will be ideal as a textbook for graduate students taking physics, engineering, or mathematical biology courses in nonlinear science or complexity.
Includes bibliographical references (p. 149-152) and index.
Keywords: Self-organized criticality (SOC).; Computer models of SOC; Mathematical formalisms of SOC